Maternal risk factors associated with intrauterine growth restriction: hospital based study - Neetika Ashwani; Aruna Rekha Neela; Suresh Mendu Babu; Suresh Kumar C.; O. Tejo Pratap (International Journal of Medical Research and Review, 2016)
Objective: To study the maternal risk factors of intrauterine growth restriction.Methods: A retrospective analysis was done at a tertiary care Hospital. Ninety three inborn intrauterine growth restriction cases were selected and data was collected by perusal of antenatal records. Intrauterine growth restriction was defined as occurring if birth weight of the newborn is below 10th percentile for gestational age on the intrauterine growth curve based on Fenton’s charts.Results: Mean age of the mothers included in the study was 20.2 ± 2.857 years. Forty four (47.3%) were born to primipara and 49 (52.7%) to multigravida. Younger maternal age, multiparity were found to be the significant socio-demographic factors associated with Intrauterine growth restriction while, pre eclampsia, chronic hypertension and anemia were the maternal biological factors found to be significantly associated on bivariate analysis.Conclusions: Younger age, multigravida and chronic medical illnesses are the main risk factors in this hospital based population. Inclusion of prenatal education and screening for medical disorders in antenatal care guidelines will help in curtailing the incidence of IUGR.